Software architecture hour with Neal Ford. (O'Reilly Media, Inc., 2022)
Join us for a special conversation with Neal Ford and solutions architect Sonya Natanzon, where they'll discuss the goal of an architect: making the invisible visible. You'll dive into the unique challenge that the complexities of healthcare pose for software architects and discover how to address them to create robust solutions and improve user experience in ways that are applicable not just to healthcare but across many industries that grapple with similar challenges. You'll learn some simple and pragmatic approaches to architectural metrics that can help your business achieve the desired outcomes in these complex domains. Neal and Sonya will talk about architecture and their own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Understand the unique challenges that healthcare poses for software architects and how to address them See what's coming next with software architecture This recording of a live event is for you because... You want to learn about architecture in healthcare and other challenging business domains. You're looking for ways to improve your architecture. Recommended follow-up: Read Software Architecture Metrics (book) Read Learning Domain-Driven Design (book) Read Fundamentals of Software Architecture (book) Read Software Architecture: The Hard Parts (book) Watch How Thoughtworks and Open GI Used 4 Key Metrics to Succeed with Their Digital Transformation (case study) Attend Software Architecture Superstream: Software Architecture Fundamentals (live online event on September 28).